FOREIGN EXPERIENCE IN PUBLIC SECTOR (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Community orientation plays an important role in modern society. This field mainly includes activities aimed at solving social problems, protecting the interests of community members and improving their quality of life. Foreign experiences show how effective strategies can be applied in public orientation. In this article, we will analyze foreign experiences in the direction of the public and discuss how they can be applied to Uzbekistan.